Noises Cancelling Adaptive Methods in Control Telemetry Systems of Oil Electrical Submersible Pumps - Ustun, O.; Yilmaz, M.; Ali Zada, P.; Tuncay, R.N. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2015)
The main ideas of this paper are that only some from more than 10 MATLAB Adaptive Methods library may be useful and can be recommended to filter out High-Noises in similar Control Telemetry Channels of Electric Power Components like ESP Systems: only four of applied have shown successfully good results in the early prediction of the ESP motor real insulation disruption (like Signerror, Sign-data and Sign-sign filters). The best among the ten analyzed adaptive filter algorithms was recognized to be, The Normalized LMS FIR filter algorithm — adaptfilt.nlms. Основная идея этой работы заключается в выборе наиболее эффективных адаптивных методов фильтрации сигналов, которые реализованы в MATLAB (из числа более десяти). Сигналы характеризуются высоким содержанием шумов, поскольку они передаются по каналам электропитания погружных электронасосов ПЭД. Исследования показали эффективность применения четырех библиотек адаптивных методов при решении задач прогнозирования состояния изоляции двигателя с целью предотвращения возможных разрушений. Наиболее эффективным адаптивным алгоритмом фильтрации для рассматриваемых задач является Normalized LMS FIR filter algorithm — adaptfilt.nlms.